Struggling for normality : experiences of patients with diabetic lower extremity amputations and post-amputation wounds in primary care - Zhu, Xiaoli (2020)
Aim: To explore the experiences of patients living with diabetic lower extremity amputation (DLEA) and its post-amputation wound in primary care.